Women and Youth Empowerment in the Agricultural Sector in Côte d’Ivoire - Yeo, P.; Arouna, A.; Mujawamariya, G.; Yergo, W.; Aboudou, R.; Gbede, T.R. (Africa Rice Center, 2023)
This report presents the results of the quantitative survey on women and youth empowerment in the agricultural sector in Côte d'Ivoire. The survey targeted producer households from a digital database established as part of the TAFS-WCA baseline study. Data were collected in five Ivorian regions from a total sample of 410 actors. The analyses focused on perceptions of decision-making authority over resources, production activities, revenues, and leadership. Particular attention is paid to the disparities between women and men and between age groups. The key results are as follows: • While men participation in decision-making on family matters is generally higher than that of women, it appears to be lower among young people than among seniors, except for education and bank account opening. • Women are less likely to own a farm property than men. Apart from agricultural innovations and processing equipment, the level of ownership of agricultural items among young people remains lower compared to that of older people. • Men have easier access than women to extension services (5.11 per cent compared to 1.71 per cent), credit (17.61 per cent compared to 11.11 per cent) and information (22.16 per cent compared to 14.10 per cent). Similarly, young people have more access to agricultural services than their elders, except for access to information and the Internet. • Women (56.41%) have less freedom to express themselves than men (65.34%), unlike seniors (62.45%) compared to young people (57.23%). Similarly, the level of women and young people who always feel comfortable expressing their disagreement is lower than that of men and older people, respectively. • Overall, women are less involved than men in decision-making about their production activities, as are young people compared to older people. • Seed production, agricultural processing and wage employment are the activities in which women earn more income than men. On the other hand, young people earn more than older people in the processing of agricultural produce and wage employment. • The contribution of older people to decisions on seed production and salaried employment is lower than that of young people, but when it comes to processing agricultural produce, women (79.31%) have a better participation in income decisions than men (70.83%). • In general, statistics confirm low leadership among women and youth in the agricultural sector. They are less represented in associations and have very little access to political positions in their communities.